ADAPTED CRITERIA AND A MODEL OF EVALUATION CHECKLIST FOR ENGLISH COURSEBOOKS - Nurdiana Nurdiana Nurdiana (Journal of Language, Literature and Teaching, 2021)
Materials/coursebook evaluation is one of the features in materials development. It is imperative to conduct materials evaluation in order to examine whether the materials covered in the coursebooks are in accordance with teaching objectives, in line with learners’ needs, suits the learners’ background and above all, whether it is devised on the principles of language learning basis.  Evaluation checklists—the instrument used to evaluate the materials—have been developed during the past few years; however, they might need revising as the items in the checklist have not represented aspects which should be assessed such as the incorporation local cultures. For this reason, the current study attempted to propose adapted criteria and a model of evaluation checklist which expectedly suit English coursebooks both local and international English coursebooks. 19 respondents were involved in this research to try out the adapted checklist. In addition, they were required to give some feedback on the items of the checklist. The results have indicated that evaluation checklist items embody the paramount aspects of English language teaching and learning and integrate items representing local English coursebooks written by Indonesian authors and those written by non-Indonesian writers.  Although the reliability and the validity of the checklist were not investigated, the proposed checklist might be worth trying to evaluate both local and international English cousebooks.